Feasibility and safety of mass drug coadministration with azithromycin and ivermectin for the control of neglected tropical diseases: a single-arm intervention trial. Issue 10 (October 2018) - Romani, Lucia; Marks, Michael; Sokana, Oliver; Nasi, Titus; Kamoriki, Bakaai; Wand, Handan; Whitfeld, Margot J; Engelman, Daniel; Solomon, Anthony W; Steer, Andrew C; Kaldor, John M
Summary: Background: Mass drug administration has made a major contribution to the public health control of several important neglected tropical diseases. For settings with more than one endemic disease, combined mass drug administration has potential practical advantages compared with separate programmes but needs confirmation of feasibility and safety. We undertook a study of mass drug administration in the Solomon Islands for trachoma and scabies control using ivermectin and azithromycin, key drugs in the control of neglected tropical diseases worldwide. Methods: The entire population of Choiseul province, Solomon Islands, was eligible to participate. An azithromycin-based mass drug administration regimen was offered in line with standard recommendations for trachoma elimination (oral azithromycin or topical tetracycline). An ivermectin-based mass drug administration regimen was offered at the same time (oral ivermectin or topical permethrin), with a further dose 7–14 days later, using a modified version of a regimen demonstrated to be effective for scabies control. All participants underwent safety assessments 7–14 days later. Participants in ten randomly selected sentinel villages underwent a more detailed safety assessment. Routine health system reports of hospital or clinic admissions and deaths were also obtained to compare health outcomes in the 12 month period before and after the mass drug administration. Findings: The study enrolled 26 188 participants, 99·3% of the estimated resident population as determined at the 2009 census. Of those enrolled, 25 717 (98·2%) received the trachoma regimen and 25 819 (98·6%) received the first dose of the scabies regimen between Sept 1, and Oct 2, 2015. A second dose of the scabies regimen was received by 21 931 (83·7%) of participants. Adverse events, all mild and transient, were recorded in 571 (2·6%) of the entire study population and 58 (4·1%) of participants in the ten sentinel villages. In the 12 months before and after the mass drug administration the numbers of hospital admissions (1530 vs 1602) and deaths (73 vs 83) were similar. In the month after the mass drug administration, 84 individuals were admitted to hospital and two died, compared with a monthly median of 116 admissions (IQR 106–159) and six deaths (IQR 4–7) in the 12 months before and after the mass drug administration. Interpretation: In the largest trial so far involving coadministration of regimens based on ivermectin and azithromycin, the combination was safe and feasible in a population of more than 26 000 people. Coadministration of mass drug administration based on these two drugs opens up new potential for the control of neglected tropical diseases. Funding: International Trachoma Initiative, Murdoch Children's Research Institute, Scobie and Claire Mackinnon Trust, Wellcome Trust.